Low-cost Posterior C1–C2 Fusion Using Sublaminar Wiring in Neurologically Intact Young Patient with Type IIA Odontoid Fracture: A Resource-oriented Approach - Novondo, Carlos; Alas-Pineda, César; Pacheco, Anahi Gisselle; Reyes-Guardado, Clarisa L.; Gaitán-Zambrano, Kristhel (Journal of Neurological Surgery Reports, 2025)
To present a low-cost posterior cervical fixation technique using sublaminar wiring for the management of a comminuted odontoid fracture (type IIA) in a young, neurologically intact patient, emphasizing its relevance in low-resource environments where advanced instrumentation is inaccessible.A 21-year-old male sustained a comminuted fracture of the odontoid process of C2 following a high-impact motorcycle accident. Upon admission, he was alert, fully oriented, and neurologically intact. Imaging revealed a comminuted type IIA odontoid fracture without displacement. Due to the patient's economic limitations and the unsuitability of the fracture for anterior fixation, a posterior approach using double sublaminar wiring between C1 and C2 with autologous iliac crest bone graft was performed.The procedure was successfully completed with no intraoperative or postoperative complications. The patient was discharged on postoperative day 2 and demonstrated excellent recovery. Follow-up imaging at 3 months confirmed over 90% fracture consolidation. Imaging at 6 months was requested but not obtained due to loss of follow-up. Functional recovery was complete, with only a partial reduction in cervical range of motion as expected with C1–C2 fusion.Sublaminar wiring offers a safe, effective, and affordable alternative for posterior fixation of comminuted odontoid fractures, particularly in young patients and in settings where access to advanced spinal instrumentation is limited.
Keywords: odontoid fracture; C2 fracture; sublaminar wiring; cervical spine trauma; case report; low-cost spinal surgery